Mapping Pesantren Economy Research in Islamic Economics: A Bibliometric Review of Trends, Themes, and Future Agenda - Purnama Putra; Endang S. Priyatna (SAN Scientific, 2026)
This study analyzes publication trends, intellectual structures, and research gaps in the field of pesantren economics using a bibliometric approach. The expanding role of Islamic boarding schools (pesantren) in community empowerment, entrepreneurship, Islamic social finance, and sustainable economic development has attracted increasing scholarly attention, highlighting the need for a systematic mapping of the literature. Data were collected from the Scopus database using the search string “Islamic boarding school economy,” covering publications from 2003 to 2024. After screening English-language documents indexed in Scopus and directly related to the economic roles, empowerment, entrepreneurship, and development functions of pesantren, 38 publications were selected for analysis. Bibliometric analysis was conducted using the Biblioshiny package in RStudio to examine publication productivity, influential authors, source journals, keyword dynamics, and thematic evolution. The results identify IOP Conference Series: Earth and Environmental Science as the most productive source and Kosim M. as the most productive author. Dominant research themes include pesantren, community empowerment, entrepreneurship, and Islamic education, while digital transformation, halal value chains, sustainability, and Islamic social finance remain underexplored. This study provides the first comprehensive bibliometric mapping of pesantren economics, offering directions for future research and policy development to strengthen pesantren's role in Indonesia’s Islamic economic ecosystem.